AKTIVITAS ANTIBAKTERI SENYAWA FLAVONOID DARI KULIT AKAR AWAR-AWAR (Ficus septica Burm F) - Sukadana, I M. (Jurnal Kimia (Journal of Chemistry), 2012)
Isolation of flavonoid antibacterial compounds from Awar-awar root skin (Ficus septica Burm.f) has been carried out. As much as 120.0 g of concentrated methanol extract was resulted from 3.9 kg dry powder of Awar-awar root skin. About 60.0 g of this extract was dissolved into 2 N hydrochloride acid and then partitioned with chloroform. Extraction of the acid extract using chloroform resulted in 0.82 g of chloroform concentrated extract which contained flavonoids. Further, the separation of this extract using column chromatography resulted in 8 fractions namely F1, F2, F3, F4, F5, F6, F7 and F8 fraction. The result of flavonoid test of the eight fractions suggested that F2, F5, and F6 fractions contained flavonoid compounds. The purification of F2 fraction using n-hexane obtained 2 fraction F2.1 and F2.2 (0.13 g and 0.01 g respectively). Infra red and ultra violet-visible spectroscopy were employed in order to identify the F2.1 fraction. From infra red spectra, it was identified that the isolate had –OH, C=O, C=C and C-H aromatic and C-H aliphatic. The ultra violet-visible spectra showed 2 peaks at 328.6 nm (band I) and 281.5 nm (band II) which indicated flavonoid class compounds flavanon or dihidroflavonol. By using ”shitting” reagent the isolate was suggested to contain flavanon group with hydroxy groups at C-2’, C-5’ or C-6’ and C-8, and methyl or glycosilacy goups at C-5 and C-7 atom. The isolate flavanon showed antibacterial activity toward Vibrio cholera and Eschericia coli.
Keywords: Ficus septica Burm f., flavanon, antibacterial, isolation, identification